An Anti‐C1s Monoclonal, TNT003, Inhibits Complement Activation Induced by Antibodies Against HLA. Issue 8 (22nd April 2015) - Thomas, K. A.; Valenzuela, N. M.; Gjertson, D.; Mulder, A.; Fishbein, M. C.; Parry, G. C.; Panicker, S.; Reed, E. F.
<x xml:space="preserve">Abstract</x> Antibody‐mediated rejection (AMR) of solid organ transplants (SOT) is characterized by damage triggered by donor‐specific antibodies (DSA) binding donor Class I and II HLA (HLA‐I and HLA‐II) expressed on endothelial cells. While F(ab′)2 portions of DSA cause cellular activation and proliferation, Fc regions activate the classical complement cascade, resulting in complement deposition and leukocyte recruitment, both hallmark features of AMR. We characterized the ability of an anti‐C1s monoclonal antibody, TNT003, to inhibit HLA antibody (HLA‐Ab)‐induced complement activation. Complement deposition induced by HLA‐Ab was evaluated using novel cell‐ and bead‐based assays. Human aortic endothelial cells (HAEC) were cultured with HLA‐Ab and human complement; production of activated complement proteins was measured by flow cytometry. Additionally, C3d deposition was measured on single antigen beads (SAB) mixed with HLA‐Ab and human complement. TNT003 inhibited HLA‐Ab mediated complement deposition on HAEC in a concentration‐dependent manner; C3a, C4a and C5a anaphylatoxin production was also diminished by TNT003. Finally, TNT003 blocked C3d deposition induced by Class I (HLAI‐Ab)‐ and Class II (HLAII‐Ab)‐specific antibodies on SAB. These data suggest TNT003 may be useful for modulating the effects of DSA, as TNT003 inhibits complement deposition and split product formation generated by HLA‐I/II‐Ab in vitro.